2020
DOI: 10.1111/jch.13986
|View full text |Cite
|
Sign up to set email alerts
|

Association between ambulatory blood pressure variability and frailty among older hypertensive patients

Abstract: Frailty is a multifactorial geriatric syndrome. The age-related cumulative decline across interrelated physiological systems and impaired homeostatic reserves results in the increased vulnerability to stressors, especially exposed to acute or chronic illness. 1,2 Accordingly, older adults with frailty are related to an increment risk for the adverse health outcomes, including falls, 1 institutionalization, 3 delirium, 4 disability, 5 and mortality. 6 It was estimated that the prevalence rate of frailty was 19.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 51 publications
2
16
0
2
Order By: Relevance
“…Hypertensive respondents constituted nearly Open access 30% of the sample, and it is of great significance to verify the association between their BP and frailty risk. Our results revealed that a higher risk of frailty was associated with poorly controlled BP among respondents with hypertension, consistent with studies of Zhu et al 8 and Woo et al, 10 which indicated the BP variability was risk factor associated with higher-order frailty status. Compared with those two studies, our study assessed the association of frailty risk with general control status of BP over a relative period, and further indicated that intensive control of BP could influence the trajectory of frailty according to both longitudinal and cohort analyses.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Hypertensive respondents constituted nearly Open access 30% of the sample, and it is of great significance to verify the association between their BP and frailty risk. Our results revealed that a higher risk of frailty was associated with poorly controlled BP among respondents with hypertension, consistent with studies of Zhu et al 8 and Woo et al, 10 which indicated the BP variability was risk factor associated with higher-order frailty status. Compared with those two studies, our study assessed the association of frailty risk with general control status of BP over a relative period, and further indicated that intensive control of BP could influence the trajectory of frailty according to both longitudinal and cohort analyses.…”
Section: Discussionsupporting
confidence: 92%
“…Poorly controlled BP can predict many advanced disease and adverse outcomes including cognitive decline, falls, morbidity (cardiovascular disease, strokes, heart failure and chronic kidney disease, etc) and so on. 8 36–38 This can partly explain the negative association between poor BP control and higher frailty risk, as frail older individuals accumulate more deficits and undergo more adverse events as age increases. However, the pathophysiological mechanisms between them are complex and not fully understood and need to be determined through more prospective studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 13 , 14 , 15 , 16 Studies have indicated that older patients have higher nighttime systolic BP as well as a reduced dipping and we hypothesize that these findings might be influenced by frailty. 8 , 17 …”
Section: Introductionmentioning
confidence: 99%